PERAN KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN RESTORAN CEPAT SAJI MCDONALD - tumpal janji sitinjak (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2017)
The higher level of competition, will cause customers to face more product alternatives, prices and quality varies, so that customers will always find the highest perceived value of some products. This purpose of this research is to analyze the influence of the quality of service and product quality to customer satisfaction at the McDonald's in Kelapa Gading. The population is customers who've bought and ate at McDonald's in Kelapa Gading. Research samples were 107 respondents were drawn at random . The procedure used to test the model and data processing is a Structural Equation Modeling using Lisrel 8.80 application. The results showed that service quality had positive and significant influence on customer satisfaction, and product quality had positive and significant influence on customer satisfaction.